2019
DOI: 10.9758/cpn.2019.17.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Asenapine in Schizophrenia Resistant to Clozapine Combined with Electroconvulsive Therapy: A Case Report

Abstract: Schizophrenic patients resistant to antipsychotics are diagnosed as having treatment-refractory schizophrenia, and they are treated with clozapine. However, clozapine is sometimes combined with electroconvulsive therapy (ECT) if clozapine monotherapy fails. In this report, a severe treatment-refractory schizophrenic patient who did not respond to clozapine even with ECT, but who recovered with asenapine monotherapy, is presented. Asenapine, considered a serotonin spectrum dopamine modulator, is a new atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several case reports have described asenapine’s high efficacy for patients with severe psychopathology including DSP [ 6 , 7 , 25 ]. The reported patients were all treated with asenapine 20 mg; the chlorpromazine equivalent- dose is 800 mg. Our present two patients’ symptoms were also successfully controlled with similar dose of asenapine.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have described asenapine’s high efficacy for patients with severe psychopathology including DSP [ 6 , 7 , 25 ]. The reported patients were all treated with asenapine 20 mg; the chlorpromazine equivalent- dose is 800 mg. Our present two patients’ symptoms were also successfully controlled with similar dose of asenapine.…”
Section: Discussionmentioning
confidence: 99%
“…This was the second head-to-head trial, where also asenapine proved its efficacy and safety. A case report published by Ochi et al [30] in 2019, showed Efficacy of Asenapine in Schizophrenia patient resistant to Clozapine combined with Electroconvulsive Therapy. A severe treatment-refractory schizophrenic patient who did not respond to clozapine even with ECT, but recovered with asenapine monotherapy gradually.…”
Section: Discussionmentioning
confidence: 99%